Pulverisation of calcified and non-calcified gall bladder stones: extracorporeal shock wave lithotripsy used alone. Issue 3 (March 1994) - Soehendra, N; Nam, V C; Binmoeller, K F; Koch, H; Bohnacker, S; Schreiber, H W
Abstract : Using a modified electromagnetic lithotripter (Siemens), extracorporeal shock wave lithotripsy (ESWL) was performed in 260 patients with gall bladder stones. Exclusion criteria for treatment were a non-functioning gall bladder, subcostal gall bladder location, and multiple stones occupying more than three quarters of the gall bladder volume. Stone pulverisation was the end point of ESWL. The number of shock wave discharges and sessions was not limited. Pulverisation was achieved in 250 patients (96.1%) after a median of three ESWL sessions (range 1-21). The number of sessions required depended upon stone composition and burden. More than three sessions were required in 60.2% of patients with calcified stones compared with 35.9% of patients with non-calcified stones (p < 0.001). 65.8% of patients with stones measuring more than 30 mm in total diameter required more than three sessions compared with 42.9% of patients with a stone burden less than 30 mm (p < 0.01). At 18-24 (8-12) months follow up, stone clearance was achieved in 94.3% (80.4%) of patients with non-calcified stones, compared with 89.5% (76.8%) in patients with calcified stones and in 75% (71.4%) of patients with a total stone diameter more than 30 mm compared with 95.7% (80.4%) for patients with a total stone diameter less than 30 mm (p < 0.05). ESWL related complications (gross haematuria) occurred in three patients. Thirty six (13.8%) patients experienced biliary colic; four had cholecystectomy, and five endoscopic papillotomy because of common bile duct obstruction. Stone recurrence was seen in 5.3% of patients over a follow up period of up to two years (median 16.6 months).